Impairments in signaling cascades mediating the progression of liver disease from chronic hepatitis to hepatocellular carcinoma in animal and human models - Setshedi, Mashiko (Department of Medicine, 2015)
The most common risk factors for chronic liver disease, cirrhosis, and hepatocellular carcinoma (HCC) include chronic alcohol abuse and infection with hepatitis B (HBV) or hepatitis C (HCV) virus. Growing evidence from human studies and experimental models suggests that pre-degenerative and premalignant abnormalities include disturbances in intracellular signaling and ongoing injury with oxidative stress, inflammation, and lipotoxicity. The major signal transduction pathways affected in both degenerative and neoplastic disease states in liver include: insulin/IGF, Wnt/β-catenin, and others.